2014
DOI: 10.1158/1541-7786.mcr-13-0300
|View full text |Cite
|
Sign up to set email alerts
|

NEDD9 Depletion Leads to MMP14 Inactivation by TIMP2 and Prevents Invasion and Metastasis

Abstract: The scaffolding protein NEDD9 is an established pro-metastatic marker in several cancers. Nevertheless, the molecular mechanisms of NEDD9 driven metastasis in cancers remain ill defined. Here, using a comprehensive breast cancer (BCa) tissue microarray, it was show that increased levels of NEDD9 protein significantly correlated with the transition from carcinoma in situ to invasive carcinoma. Similarly, it was shown that NEDD9 overexpression is a hallmark of highly invasive BCa cells. Moreover, NEDD9 expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…Overexpression of NEDD9 in MDA-MB-453 and ZR75-1 BC cells with low endogenous expression of NEDD9 using a doxycycline inducible system led to a significant increase in migration (Fig.1K–L). In addition to the decrease in 2D migration, NEDD9-depleted cells exhibited up to 60% decrease in 3D migration/invasion through matrigel (Fig.S1C), confirming our previous observations [7]. The decrease in cell migration could be due to the impairment in cell adhesion to certain components of the ECM.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Overexpression of NEDD9 in MDA-MB-453 and ZR75-1 BC cells with low endogenous expression of NEDD9 using a doxycycline inducible system led to a significant increase in migration (Fig.1K–L). In addition to the decrease in 2D migration, NEDD9-depleted cells exhibited up to 60% decrease in 3D migration/invasion through matrigel (Fig.S1C), confirming our previous observations [7]. The decrease in cell migration could be due to the impairment in cell adhesion to certain components of the ECM.…”
Section: Resultssupporting
confidence: 90%
“…Overexpression of the NEDD9 protein is known to promote migration/invasion in multiple cancers [5, 7, 8]. We have recently reported that depletion of NEDD9 leads to a significant decrease in breast cancer metastasis due to inactivation of MMPs [7] and migration deficiency, but the molecular mechanisms of the phenomenon are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ILK recruits the scaffold protein IQGAP to invadopodia to induce membrane type-I MMP (MT1-MMP) exocytosis, while NEDD9 limits the accumulation of tissue inhibitor of metalloproteinase-2 (TIMP2), an endogenous MT1-MMP inhibitor, at invadopodia to promote MT1-MMP-mediated matrix degradation (Branch et al, 2012; McLaughlin et al, 2014). Taken together, adhesion proteins regulate invadopodium maturation by enhancing actin polymerization and MMP-mediated matrix degradation, while having limited effects on invadopodium precursor assembly.…”
Section: Invadopodium Maturationmentioning
confidence: 99%